How do fluctuations in endogenous sex hormones affect breast pain in female athletes? - Brisbine, B. R.; Mara, J. K.; McKay, A. K. A.; Burke, L. M.; McCormick, R.; Harris, R.; Minahan, C.; Ackerman, K. E.; Coltman, C. E. (Scandinavian Journal of Medicine & Science in Sports, 2025)
Cyclic breast pain (mastalgia) is speculatively associated with hormonal fluctuations during the menstrual cycle. No research to date has quantified this effect through circulating concentrations of estradiol and progesterone in a sample of female athletes. Such data are essential for understanding how hormonal changes contribute to the incidence and severity of cyclic breast pain, with implications for enhancing breast pain management and athletic performance in women's sport. Twenty-four female Australian First Nation athletes from the National Rugby League Indigenous Women's Academy pathways program participated in a Female Athlete Research Camp. Over 5 weeks, participants completed a daily survey about their experience of breast pain and, at three approximate phases of the menstrual cycle (Phases 1, 2, and 4), presented to the laboratory for venous blood samples to track circulating estradiol and progesterone concentrations. Average mastalgia ratings spiked during the commencement of the menstrual period and 14-26 h prior to ovulation. Higher levels of estradiol and progesterone were associated with a decreased likelihood of experiencing mastalgia; elevated progesterone levels were also linked to a reduction in mastalgia severity. These effects were highly interdependent, such that the effect that progesterone had on mastalgia was dependent on the value of estradiol, and vice versa. This study provides the first quantitative evidence that circulating estradiol and progesterone levels influence the occurrence and severity of cyclic breast pain in female athletes. These findings support the development of targeted strategies for managing mastalgia, ultimately promoting well-being and enhancing performance for women in sport.